Prevalence of constipation among persons living in institutional geriatric‐care settings – a cross‐sectional study. Issue 1 (21st June 2016) - Lämås, Kristina; Karlsson, Stig; Nolén, Anna; Lövheim, Hugo; Sandman, Per‐Olof
Abstract : Rational: The current state of knowledge about the prevalence of constipation among persons living in institutional geriatric‐care settings is limited. Aim: The aim was to investigate the prevalence of constipation among institutional geriatric‐care residents and identify resident characteristics related to constipation. Methodological design: In a cross‐sectional study of all the institutional geriatric‐care settings in a county in northern Sweden, 2970 residents were assessed. The member of staff who knew each resident best used the Multi‐Dimensional Dementia Assessment Scale and the resident's records of prescribed medication to monitor cognitive function, activities in daily life, behavioural and psychological symptoms, physical restraints, speech ability, nutrition and pharmacologic agents. The study was approved by the Regional Ethical Review Board. Result: The prevalence of constipation was 67%. The mean age was higher among those with constipation. A significantly higher proportion of the constipated had cognitive and/or physical impairments, physical restraints, impaired speech, problems with nutrition, and higher numbers of drugs for regular use. Of those with constipation, 68% were prescribed laxatives for regular use. Twenty‐three per cent of the constipated residents were prescribed opioid analgesics (n = 465), and 29% (n = 134) of these were not prescribed any laxatives. Study limitation: Due to the cross‐sectional design, the results should be interpreted with caution in terms of causal reasoning, generalisation and conclusions about risk factors. Another limitation is the use of proxy assessments of constipation. Conclusion: The results show that constipation is common among residents in institutional geriatric‐care settings in Sweden, which is in line with previous studies from other Western countries. Despite being constipated when having prescribed opioid analgesics, a large number did not have prescribed laxatives. The results indicate the urgency of finding strategies and implementing suitable interventions to improve bowel management in residents in institutional geriatric‐care settings.